Effect of Acid-Hydrolyzed Thermoplastic Starch on the Mechanical, Thermal and Morphological Properties of Polyethylene Based Composites - Ramírez, Perla Mayari Trejo; Hernández-Hernández, Ernesto; Rosas, Javier Castro; Solís-Rosales, Silvia Guadalupe; Villagómez-Ibarra, José Roberto; Gómez-Aldapa, Carlos Alberto (Journal of Research Updates in Polymer Science, 2016)
The effect of the addition of hydrolyzed thermoplastic maize starch on the physico mechanical properties of low-density polyethylene (LDPE)-based composites was studied. Acid-hydrolyzed native starch was thermoplasticized using 15 and 30% glycerol in weight relative to starch, after which the LDPE/thermoplastic starch (TPS) composites were prepared at TPS concentrations of 10, 25, and 50%. According to the results of Raman spectroscopy, the appearance of a new band at 756 cm-1 was observed, and it was attributed to the hydrolysis process and associated with the C-C-O vibrational modes of the glycosidic bond. The addition of both native and polyethylene hydrolyzed TPS reduced the Young’s modulus of the composites; but the reduction was greater for those containing native starch. Both the maximum stress and deformation decreased to a greater degree for the composites with hydrolyzed TPS. The composites containing TPS prepared with 15% glycerol exhibited a higher Young’s modulus compared to those with LDPE, although they exhibited fragile behavior. The degree of matrix crystallinity increased with the addition of TPS and showed the largest increase when TPS 50% hydrolyzed by weight was added, showing an increase of 35%. It was observed that the size of the TPS particles, both native and hydrolyzed, increased in size as the concentration of TPS in the matrix increased. The size of the hydrolyzed TPS particles was greater than that of the native TPS particles, and in the case the of the hydrolyzed TPS particles, some exhibited an ellipsoidal and/or fibrillar morphology.